“Same same” but different? Exploring the impact of perceived organizational support at the school and teacher levels on teachers’ job engagement and organizational citizenship behavior - Hsieh, Chuan-Chung; Chien, Wei-Cheng; Yen, Hung-Chin; Li, Hui-Chieh (Frontiers in Psychology, 2022)
This study explored the relationships between school organizational support (SOS), job engagement (JE) and organizational citizenship behavior (OCB) in an educational context. In particular, perceived organizational support (POS) was examined at the individual level and the aggregated school level. Analysis was performed using structural equation modeling (SEM) at both single and multiple levels. SEM results showed direct and positive relationships of individual-level POS with both JE and OCB. Moreover, JE is directly and positively related to OCB and plays the partial mediating role of the indirect and positive impact of POS on OCB. Multilevel structural equation modeling (MSEM) analysis revealed direct and positive relationships of SOS with teachers’ JE, which was directly and positively related to their OCB. While SOS had no significant positive relationship with OCB, it did have a positive impact on OCB through the mediation of JE. Comparison between SEM and MSEM results revealed the change in effect of OS on OCB from significant to insignificant, thus implying full mediation effect of JE when SOS is considered.